The Relationship Between Financial Leverage And Quick Ratio In The Private Banks Listed On The Damascus Securities Exchange - مرهج, منذر (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aimed to discover the relationship between the degree of financial leverage resulting from the increase in the volume of deposits deposited by customers in the bank, and the degree of quick liquidity that the bank needs to meet its obligations related to the payment of interest on deposits or to meet requests for withdrawal from them or to meet borrowing requests by customers. The research relied on the descriptive analytical approach. The research community included all fourteen private banks listed on the Damascus Securities Exchange, where the necessary secondary data related to the studied banks were collected from the website of the Damascus Securities Exchange, and the research also relied on cross-sectional data analysis for the fourteen study community vocabularies during the period 2010-2018, depending on the random-effects model, which statistical tests conducted for this purpose proved to be the appropriate model among the basic models for analyzing cross-sectional time series data (fixed-effects model, random-effects model, and Pooled regression model). The research reached a set of results stating that there is an inverse and significant relationship between the ratio of financial leverage and the ratio of quick liquidity in the studied banks, which means that with the increased attractiveness of the studied banks to more deposits and the high degree of financial leverage in them, it did not work to increase the rates of quick liquidity enough to cover the liquidity risk that these banks may be exposed to, in order to achieve more profits and increase the level of profitability as one of the main objectives of the bank.